Enhancing induced flow rate through a solar chimney by a forced flow. Issue 1 (March 2021) - Nguyen, Y Q
Abstract: Solar chimneys absorb solar radiation for natural ventilation or cooling of buildings. In typical solar chimneys, the air flow is induced by the thermal effect which causes pressure gradient inside the chimney to deviate from that of the ambient air. The induced flow is employed to ventilate the connected building naturally. In this study, we aimed to boost the induced flow rate through a typical solar chimney by a forced flow at the inlet of the air channel which is divided into two ports for the forced and the induced flows. The air flow and heat transfer were modeled with a Computational Fluid Dynamics (CFD) model with the ANSYS Fluent CFD code. Changing factors included the forced velocity, the dimensions of the inlet port for the forced air flow and the length of the partition between the ports of the naturally induced and forced air flows. It is seen that the forced flow significantly reduces the pressure in the air channel compared to that of a typical chimney; hence increasing the induced flow rate. The flow rate was significantly enhanced as the forced velocity was above 0.2 m/s; the area of the inlet port for the forced flow was 12.4% of the total inlet area; and the partition height was less than 5.0% of the total height of the air channel. In this configuration, the forced flow can be the waste exhaust air flow from other mechanical ventilation systems of the building. Therefore, no additional energy is required for this solution.